2018
DOI: 10.1088/1361-6463/aacc3d
|View full text |Cite
|
Sign up to set email alerts
|

Methane/nitrogen plasma-assisted synthesis of graphene and carbon nanotubes

Abstract: An experimental and numerical study of plasma-assisted synthesis of graphene and carbon nanotubes is presented. Experiments were carried out using methane/nitrogen plasma generated by a DC plasma torch with pressure variation in the 100–710 Torr range. The synthesis products were studied by synchronous thermal analysis and scanning electron microscopy. The results of these experiments are shown in thermogravimetry graphs and snapshots of the synthesized structure morphology. It is shown that structures in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Shavelkina et al. [ 124 ] directly fabricated graphene and CNTs doped with nitrogen using a CH 4 ‐N 2 direct current (DC) plasma at pressures of 100–700 Torr. The N content of the CNTs reached up to 8 at%, and the formed graphene flakes displayed high thermal stability.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Shavelkina et al. [ 124 ] directly fabricated graphene and CNTs doped with nitrogen using a CH 4 ‐N 2 direct current (DC) plasma at pressures of 100–700 Torr. The N content of the CNTs reached up to 8 at%, and the formed graphene flakes displayed high thermal stability.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…Thus, it has been experimentally shown that using the DC plasma torch to generate the helium/propane-butane plasma jet, a highly efficient system for the graphene To analyse kinetic processes initiated in the arc plasma torch in the helium/propane-butane mixture, an approach was used similar to that described and applied in our work [18]. To determine the mixture composition in different temperature ranges in the gap between the reactor nozzle and the material collection point, we used our RADICAL software package [28][29][30] and the extended scheme of chemical reactions involving 769 reactions between 123 components.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…Previously, we have shown a possibility of the graphene synthesis using the DC plasma torch, at pressures of 100-710 Torr [18][19][20]. Varying the plasma-forming gases and the carbon sources (solid, liquid, and gaseous carboncontaining substances), the jet cooling process, and the product collecting system, graphene, hydrogen and nitrogen modified graphene, as well as carbon nanotubes were synthesised in the same reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectrum of graphane has specific peaks D, G and 2D at 1349, 1586 and 2695 nm with altered relation I D /I G (figure 5). According to [22][23][24] the relative intensity of the G-peak with respect to the 2D-peak (I G /I 2D ) along with the shape of the 2D-peak is also an indication of the number of graphene layers. The peculiarity of hydrogenated graphene synthesized by means of DC plasma torch in comparison with that in [4] is its origin in the volume of plasma jet, not as a result of the treatment of the pristine graphene with hydrogen containing medium.…”
Section: Samples Characterizationmentioning
confidence: 99%